Các yếu tố tác động tới hiệu quả hoạt động phòng chống thiên tai lũ quét ở khu vực miền núi phía Bắc, Việt Nam - Nguyễn Hữu, Dũng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper investigates the factors affecting the effectiveness of flood disasters management in the Northern mountainous provinces in order to reduce the risks caused by flood disasters. The paper uses the Ordered Logit regression model with latent variables “effectiveness of flash flood disaster prevention” is measured according to the Formative measurement component scale model. Data was collected through Provincial People’s Committees, and with 407 semi-structured questionnaires undertaken with key informants including heads of communes, elderly villagers, and local government staffs at various locations selected by flood-vulnerability stratify sampling approach in 15 Northern mountainous provinces. The analysis revealed that social factors, policy, economics, and management have less impact on the effectiveness of flood disaster management, while factors such as institution, environment, and technology have significant impacts. Among them, the institution is a critical factor for achieving the underlying functional change, and it should be reformed to internalize the community-based management.